Sister Carrie - Dreiser, Theodore, 1871-1945 (University of Pennsylvania Dreiser Edition., 1981)
The story of a young woman from Wisconsin who goes to Chicago, becomes an actress, marries and moves to New York, and when her husband loses his job, returns to the stage.